Impact of Imperialism and Western Influence on Middle East: A Case Study of Iraq and Iran - Adeseko, Adebanke Adebimtan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Imperialism, which is the practice by powerful country or group of countries gaining control over weaker one through dominance or influence, can be traced to the 18th century. Western imperialism, characterized by a colossal power inequality between the colonizers, located in the west, and the colonized, located in the East, was owing to the Middle East regions’ potentials of industrialization, geographical locations and most importantly, oil. Iraq and Iran, both situated in the Middle East, are areas blessed with a large oil deposits which made them those of the most desirable territories in the Middle East and vulnerable to western imperialism. Therefore, this study focuses on Iraq and Iran as cases study, sought to investigate the dynamics behind the rise of imperialism in the Middle East and the impacts of imperialism in this region as well as how Iraq and Iran struggled against the Western exploitation. Driven by World-System and Dependency theories, qualitative and descriptive case study method was adopted for this study. The impacts of imperialism on Iraq include current redrawing of the Iraqi borders into boundaries of Shia majority, a large Sunni minority, a Kurdish region, the creation of the state of Iraq and the high dependent of Iraq on the west, despite being an oil producing country; while Iran, though was never officially subject to imperial power, was indirectly and by proxy, ruled and controlled by the west, having had its democratically-elected leader eliminated. This study concludes that besides oil, poverty, low technological development and poor governance contributed to the rise of imperialism in the Middle East. However, despite the exploitations by the West, Iran and Iraq benefitted positively in terms of industrialization of oil industry and evolution of infrastructure. Therefore, government of developing countries should encourage self-development and self-reliance to avoid any form of imperialism. Keywords: Dependency theory, Imperialism, Iran, Iraq, Middle East, World-System Theory

ÖZ : Güçlü ülke veya ülkelerin, zayıf ülkeler üzerinde, domine etme veya etkileme yolu ile kontrol kazanma uygulaması olan emperyalizm 18.nci yüzyıla dayandırılabilir. Batıdaki kolonize edenler ile doğudaki kolonize edilenler arasındaki muazzam güç dengesizliği ile karakterize edilen batı emperyalizmi, Ortadoğu bölgesinin endüstrileşme, coğrafik yerleşimler, ve en önemlisi petrol kaynaklarını elinde tutuyordu. Ortadoğu’da bulunan İran ve Irak büyük petrol kaynakları ile donanmış olup bu kaynaklar onları Ortadoğu’da en fazla istenen, ve batı emperyalizmine karşı korumasız bir duruma getirdi. Bu nedenle bu çalışma vaka çalışması anlamında İran ve Irak üstüne odaklanmış olup emperyalizm’in Ortadoğu’daki yükselişi,bu bölgedeki etkileri, ve İran ve Irak’ın batının istismarına karşı nasıl mücadele ettiklerini anlatmaktadır. Bu çalışma için, Dünya Sistemi ve Bağımlılık teorileri tarafından yönlendirilen niteleyici ve açıklayıcı vaka çalışma yöntemleri benimsenmiştir. Emperyalizm’in Irak üzerinde etkileri halen Irak sınırının Sheia çoğunluğunun sınırının içine doğru çekilmesi, büyük bir Sünni azınlığı, bir Kürt bölgesi, petrol üreten bir ülke olmak yerine batıya çok fazla bağımlı bir ırak devleti kurulmasını ihtiva eder ; diğer taraftan İran ise resmi olarak hiç bir zaman emperyal güce bağlı olmamış, dolaylı yoldan ve vekaleten batı tarafından konrtol edilip yönetilmiş ve demokratrik yoldan seçilmiş bulunan başkanı bertaraf edilmiştir. Sonuç olarak denilebilir ki, petrolün yanısıra güç, düşük teknolojik gelişim, ve zayıf yönetimler emperyalizm’in Ortadoğu’daki yükselmesine katkı sağlamıştır. Bunun vi yanında batının istismarlarına rağmen İran ve Irak, petrol endüstrisinin büyümesi ve altyapının gelişimi konularında olumlu kazanımlar sağlamışlardır, bu yüzden gelişmekte olan ülkelerin hükümetleri ülkesel gelişim ve ülkesel güveni özendirerek emperyalizm’in her çeşitinden kaçınma yoluna gitmelidirler. Anahtar kelimeler : Bağımlılık teorisi, Emperyalizm, İran, Irak, Ortadoğu, Dünya Sistemi teorisi.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2016. Supervisor: Assist. Prof. Dr. John Turner.
Keywords: Political Science and International Relations; Imperialism - International Relations - Politics; Imperialism - Middle East - Iraq - Iran; Dependency theory; Imperialism; Iran; Iraq; Middle East; World-System Theory